The role of entrepreneurial leadership in achieving institutional excellence: A field study on the employees of the University of Tabuk (2022-1444) - Al-Roqi, Setah Mofareh; Al-Mustadi, Walaa Abdullah AbdulRahman (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to know the role of entrepreneurial leadership through its dimensions (initiative and proactive, taking risks, creativity and self-confidence) in achieving institutional excellence among the employees of the University of Tabuk. It also aimed to detect statistically significant differences about individuals' average responses between entrepreneurial leadership and institutional excellence attributable to demographic variables. The study was based on the analytical descriptive curriculum and the questionnaire was used as a data collection tool. It obtained a sample of (216) male and female employees through the simple random sample of the study population of (1274). The study found several results, which includes: There is a role for a leadership in achieving institutional excellence at the University of Tabuk from the point of view of its employees. The degree of practicing entrepreneurial leadership at the University of Tabuk is high, with an arithmetic mean of (3.52 out of 5.00), and the degree of practicing initiative and proactivity at the University of Tabuk is medium, with an arithmetic mean of (3.31 out of 5.00), and the degree of practicing taking risks at the University of Tabuk is high, with an arithmetic mean of (3.51 out of 5.00) and the degree of practicing creativity at the University of Tabuk is high, with an arithmetic mean of (3.56 out of 5.00), In addition to this, the degree of practicing self-confidence at the University of Tabuk is high, with an arithmetic mean of (3.71 out of 5.00), and the degree of institutional excellence at the University of Tabuk is high, with an arithmetic mean of (3.67 out of 5.00). There are differences in the responses of sample individuals about the relationship between entrepreneurial leadership and institutional excellence at University of Tabuk in terms of academic qualification, for the bachelor's category. Furthermore, there are no differences in the responses of sample individuals in terms of gender, age and years of experience.
Keywords: leadership; entrepreneurial leadership; excellence; institutional excellence; University of Tabuk